The Xenopus Oocyte: A Single-Cell Model for Studying Ca(2+) Signaling - Lin-Moshier, Yaping (2013)
In the four decades since the Xenopus oocyte was first demonstrated to have the capacity to translate exogenous mRNAs, this system has been exploited for many different experimental purposes. Typically, the oocyte is used either as a “biological test tube” for heterologous expression of proteins without any particular cell biological insight or, alternatively, it is used for applications where cell biology is paramount, such as investigations of the cellular adaptations that power early development. In this article, we discuss the utility of the Xenopus oocyte for studying Ca(2+) signaling in both these contexts.